Pengaruh Brand ambassador dan Keuntungan Reksa Dana Pada Minat Mahasiswa Dalam Berinvestasi Reksa Dana Pada Aplikasi Bibit (Studi Pada STIE Satya Dharma angkatan 2019). - Putu Devy Isabella Permatawati (LPPM Universitas Buana Perjuangan Karawang, 2023)
The purpose of this study was to determine the effect o f brand ambassadors and mutual fund benefits on students' interest in investing in mutual funds in Bibit applications (studies at STIE Satya Dharma class of 2019). The analysis technique used in this research is validity and reliability test, classical assumption test, multiple linear regression analysis, and model feasibility test. The results of the study show that Brand ambassadors have an effect on student interest in investing in mutual funds in the Bibit application (Study at STIE Satya Dharma class of 2019) from the results of hypothesis testing with the T test showing that Brand ambassadors have a positive and significant effect on student interest in investing in mutual funds. Profits affect student interest in investing in mutual funds in the Bibit application (Study at STIE Satya Dharma class of 2019) from the results of hypothesis testing with the T test showing that profits have a positive and significant effect on student interest in investing in mutual funds.